Soil Health: New Opportunities to Innovate in Crop Protection Research and Development - Atwood, L. W.; Racette, K. A.; Diggelmann, M.; Masala, C. A.; Maund, S.; Oliver, R.; Screpanti, C.; Wironen, M.; Wood, S. A. (Frontiers in Environmental Science, 2022)
Soil health-based agricultural management practices are widely promoted to reduce erosion, increase nutrient use efficiency, improve soil structure, and sustain or increase yields. Pest and disease management are less frequently considered as components of a soil health management system. We present a framework for how the crop protection industry can advance soil health by developing systems of crop protection innovation that simultaneously target soil health outcomes, either through direct impact on soil or by enabling practices that promote soil health outcomes. Such an approach could lead to cross-sectoral, integrated agricultural solutions that achieve agronomic, environmental, and economic goals.